Carbon capture through solar-driven CO2 gasification of oil palm empty fruit bunch to produce syngas and biochar - Saqr A. A. Al-Muraisy; Srirat Chuayboon; Laís Américo Soares; Josephus G. Buijnsters; Shahrul bin Ismail; Stéphane Abanades; Jules B. van Lier; Ralph E.F. Lindeboom (Energy, 2025)
Oil palm empty fruit bunch (OPEFB) is an abundant organic waste in Malaysia that is often disposed of through field burning. A previous study has shown that solar-driven steam gasification of OPEFB can produce hydrogen-rich syngas with an energy upgrade factor of 1.2 and a carbon conversion efficiency of 95.1 %. Beyond its potential as a biofuel, OPEFB can also act as a carbon sink, capturing photosynthetically stored carbon. This study explores the potential of amplifying OPEFB's negative carbon emissions through solar-driven gasification, using CO 2 as the gasifying agent. In this work, a Central Composite Design (CCD) approach was employed to assess the influence of temperature (1100–1300 °C) and CO 2 /OPEFB molar ratio (1.6–3.0) on H 2 /CO molar ratio and energy upgrade factor, with a constant OPEFB flow rate of 1.8 g/min. The results demonstrated that at an energy upgrade factor of 1.4, 94.9 % of the total carbon was converted into syngas with a H 2 /CO molar ratio of 0.3. The maximum observed net carbon capture yield of 0.4 g C/g OPEFB was achieved at 1300 °C and a CO 2 /OPEFB molar ratio of 3.0. The remaining carbon (94.4–95.7 wt %) was converted into biochar with low heavy metal content, which has potential as a soil enhancer. • Solar-driven CO 2 gasification of OPEFB captures carbon into syngas and biochar. • Net carbon capture reached 0.4 g C /g OPEFB , with 94.9 % carbon conversion efficiency. • H 2 /CO molar ratio achieved 0.3, equating to a high CO content of 58.5 mmol/g OPEFB . • Energy upgrade factor of syngas reached 1.4, showing efficient storage of energy. • Biochar with high carbon and low-heavy metals is ideal for soil enhancement.
Keywords: Catalysts for Methane Reforming; Thermochemical Biomass Conversion Processes; Energy and Environment Impacts